EXPLORING INDONESIAN EFL STUDENTS' EXPERIENCE IN VLOGGING FOR SPEAKING PRACTICE - Faidah Yusuf; Latri Aras; Muhammad Faisal; Ameer Ali (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTResearch on the use of digital technology in English-speaking practice has been widely acknowledged in the literature, including empirical studies on the use of vlogging as a mediated instruction in teaching speaking skills. This study aimed to investigate Indonesian EFL students' experiences when conducting a food vlog learning project in English-speaking practices. Fifty students in the Education Department at the State University of Makassar, Indonesia, took part in this study. In their English classes, they worked on the food vlog as a project-based learning (PBL) activity. Random sampling was used to choose five people from each of the five groups of ten people, and they agreed to take part in a semi-structured interview. A thematic analysis was used to look at the qualitative data from the interview. The results indicate that the food vlog group, as part of PBL, helped and enhanced the students' self-efficacy, vocabulary mastery, learning autonomy, technology skills, and confidence in speaking English in EFL classes. These findings suggest that PBL has practical application within the context of the food vlog project. Consequently, utilizing a food vlog as a learning activity can be an effective support in practicing their English-speaking skills beyond the confines of the classroom.ABSTRAKPenelitian tentang penggunaan teknologi digital dalam praktik berbahasa Inggris telah diakui secara luas dalam literatur, termasuk studi empiris tentang penggunaan vlogging sebagai instruksi mediasi dalam pengajaran keterampilan berbicara.Penelitian ini bertujuan untuk menyelidiki pengalaman siswa EFL Indonesia dalam melakukan proyek pembelajaran vlog makanan dalam praktik berbahasa Inggris. Lima puluh mahasiswa di Departemen Pendidikan di Universitas Negeri Makassar, Indonesia, mengambil bagian dalam penelitian ini. Di kelas bahasa Inggris mereka mengerjakan vlog makanan sebagai kegiatan pembelajaran berbasis proyek (PBL). Pengambilan sampel acak digunakan untuk memilih lima orang dari masing-masing lima kelompok yang terdiri dari sepuluh orang, dan mereka setuju untuk mengambil bagian dalam wawancara semi-terstruktur. Analisis tematik digunakan untuk melihat data kualitatif dari wawancara. Hasil penelitian menunjukkan bahwa kelompok food vlog sebagai PBL membantu dan meningkatkan self-efficacy siswa, penguasaan kosa kata, kemandirian belajar, keterampilan teknologi, dan kepercayaan diri dalam berbicara bahasa Inggris di kelas EFL. Temuan ini menyatakan bahwa PBL memiliki aplikasi praktis dalam konteks proyek vlog review makanan secara nyata. Oleh karena itu, food vlog dapat digunakan sebagai kegiatan pembelajaran yang efektif untuk membantu siswa berlatih berbicara bahasa Inggris di luar kelas.How to Cite: Yusuf, Y., Aras, L., Faisal, M., & Ali, A. (2023). Exploring Indonesian EFL Students Experience in Vlogging for Speaking Practice. IJEE (Indonesian Journal of English Education), 10(2), 443-462. doi:10.15408/ijee.v10i2.32036.